DIMENSI ETNO-POLITIK PEMEKARAN WILAYAH DAN PILKADA Beberapa Catatan dan Pemikiran - Riwanto Tirtosudarmo (Jurnal Masyarakat dan Budaya, 2005)
The events surrounding Suharto’s resignation in May 1998 and its aftermath pararelly followed by the occurrences of communal conflicts in several places such as Maluku, Central Sulawesi and Kalimantan. Interestingly these communal conflicts also occurred at the same time with the process of splitting of the district territories (pemekaran) that were accelerating under the implementation of the new law of decentralization and regional autonomy in 2001. This paper utilizing the political demography perspective is a preliminary attempt to look at the possible linkages between ethnodemographic configuration and the communal conflict within particular geographic administrative boundaries and its repercussions on the process of pemekaran. As the implementation of the direct election of the local governmental head (Pilkada) is currently underway the paper also provides some notes on the ethno-political dynamics of this regional version of people’s direct election. The paper argues that ethnicity is mattered in the process of pemekaran and could be manipulated by the local elites in their attempt to obtain mass support during the Pilkada. More systematic research however is needed to better understand the complex nexus between ethnicity and local politics in Indonesia.